The US Foreign Policy towards the Islamic World; Trump VSBiden - HAMIDI Narimen.KARA MAHAMMED Wafa., Dr. BOUNAAS Chaouki (UNIVERSITY OF MOHAMED BOUDIAF, 2022)
Abstract The foreign policy is commonly known as the rules that are applied by a country leader to achieve its interests, such as the United States. The policies that were adopted by the different leaders of US differ from one period to another and from one president to another. This research tried to shed a light on the history of the U.S. foreign policy towards the Islamic Worldbefore the cold war till the administration of Biden. And how the U.S. is still highly influential in the world. In the other hand, it seeks to examine the comparison between the presidents Trump and Biden in different regions in the Islamic World. As well as, this research explores the factors that would drive campaigns if they emerge as the two presidential contenders on major US foreign policyissues most regarding the Islamic World. The importance of this study lies in tackling an issue that is sensitive for the Islamic World as well as to differentiate between the strategies taken by the presidents Trump and Biden. Thus, the policies adopted by Trump’s administration were from the standpoint of managing the problem rather than resolving it. But in contrast, Biden tries to reshape US foreign policy in the Islamic World putting a premium on promoting democracy. It presents the theoretical background of US foreign policy, the evolution and the landmark events of the conflict
Keywords: Key words: Abstract, US Foreign policy, Islamic world,9/11 terrorist attack, containment policy, Interventionism, Biden administration, Trump administration, Islamic’s regions.